Analisis Pengaruh Praktik Manajemen Sumberdaya Manusia Terhadap Kinerja Guru (Studi Di Sdn Kembiritan Kabupaten Banyuwangi) - Wulan, Mutiara Octa Sandra; Wahono, Budi; Primanto, Alfian Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The aim of research using this type of explanatory research and quantitative approach is to determine and analyze the influence of recruitment, selection and training on teacher performance at SDN Kembirita, Banyuwangi Regency, both simultaneously and partially. The population of this research is all elementary school teachers in ten Kembiritan elementary schools, totaling 79 permanent teachers. The sampling technique used was a saturated sample, where all members of the population were used as a sample and a total of 79 respondents were found. This research method uses multiple linear regression analysis with SPSS analysis tools. Based on the results of this research, simultaneous and partial recruitment, selection and training have a significant influence on teacher performance at SDN Kembirita, Banyuwangi Regency. Keywords: Recruitment, Selection, Training, And Performance